The dentistry of the future: an integrated approach to family and community health - Cueto U., Alfredo (2023)
In a constantly evolving world, dentistry faces new challenges and opportunities that lead us to rethink our traditional approach. Historically, universities have played a crucial role in training oral health professionals, focusing on teaching, research, and environmental engagement. However, with the advent of digital dentistry and artificial intelligence, we imagine a landscape where certain dental activities could be automated, transforming how we approach oral health.